2016
DOI: 10.1038/srep37052
|View full text |Cite
|
Sign up to set email alerts
|

Bafilomycin A1 induces caspase-independent cell death in hepatocellular carcinoma cells via targeting of autophagy and MAPK pathways

Abstract: Hepatocellular carcinoma (HCC) is refractory to chemotherapies, necessitating novel effective agents. The lysosome inhibitor Bafilomycin A1 (BafA1) at high concentrations displays cytotoxicity in a variety of cancers. Here we show that BafA1 at nanomolar concentrations suppresses HCC cell growth in both 2 dimensional (2D) and 3D cultures. BafA1 induced cell cycle arrest in the G1 phase and triggered Cyclin D1 turnover in HCC cells in a dual-specificity tyrosine phosphorylation-regulated kinase 1B (DYRK1B) depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 20 publications
8
53
0
Order By: Relevance
“…However, Yan et al used lowdose bafilomycin A1 to block autophagic flux, which also triggered cyclin D1 turnover, but in a DYRK1Bdependent fashion, leading to the caspase-independent death of HCC cells. (25) Based on our findings and other reports, it appears that either induction or suppression of autophagy activation could trigger cyclin D1 turnover, but through different signaling pathways, which further determine the fate of the cells. Altogether, suppression of cell-cycle progression through autophagy-regulated cyclin D1 turnover may have potential as an effective therapy for HCC.…”
Section: Discussionsupporting
confidence: 72%
“…However, Yan et al used lowdose bafilomycin A1 to block autophagic flux, which also triggered cyclin D1 turnover, but in a DYRK1Bdependent fashion, leading to the caspase-independent death of HCC cells. (25) Based on our findings and other reports, it appears that either induction or suppression of autophagy activation could trigger cyclin D1 turnover, but through different signaling pathways, which further determine the fate of the cells. Altogether, suppression of cell-cycle progression through autophagy-regulated cyclin D1 turnover may have potential as an effective therapy for HCC.…”
Section: Discussionsupporting
confidence: 72%
“…As for tumor cells, V‐ATPase is a key regulator of intracellular acidification. Researchers have found that Baf‐A1 is involved in arresting the cell cycle in G1 phase, causing apoptosis, and inhibiting autophagy in a dose‐dependent manner (Yan et al, ; Yuan et al, ). In contrast, the current study showed that Baf‐A1 promoted the transition from the G1 phase to the S phase in BmE cells, so the percentage of cells in S and G 2 /M phases increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, when using inhibitors, limitations arise in determining the suitable concentration for efficient autophagy inhibition, without severely affecting cell viability. The major limitation when using inhibitors is, however, the occurrence of potential off-target or adverse effects, which could lead to misleading results 31,32 .…”
Section: Discussionmentioning
confidence: 99%